Coconut Shell Activated Carbon/CoFe2O4 Composite for the Removal of Rhodamine B from Aqueous Solution. (28th October 2020) - Hoang, Le Phuong; Van, Huu Tap; Nguyen, Thi Thuy Hang; Nguyen, Van Quang; Quang Thang, Phan
Abstract : Coconut shell activated carbon loaded with cobalt ferrite (CoFe2 O4 ) composites (CAC/CoFe2 O4 ) was synthesized via the single-step refluxing router method to manufacture adsorbents. The adsorbents were then applied to remove Rhodamine B (RhB) from aqueous environments via adsorption. The properties of coconut shell activated carbon (CAC) and CAC/CoFe2 O4 were investigated through the usage of electron microscopic methods (SEM: Scanning Electron Microscopy, EDS: Energy Dispersive X-ray), powder X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). A series of batch experiments were implemented to evaluate the influences of various experimental parameters (initial pH, RhB concentration, contact time, and dosage of CAC/CoFe2 O4 ) on the adsorption process. It was found that CoFe2 O4 was successfully attached to activated carbon particles and had the suitable adsorption capacity for RhB at a molar ratio of 1 : 2:200 corresponding to the Co : Fe:CAC order. The removal efficiency and adsorption of RhB were optimal at a pH level of 4. The maximum adsorption capacity was 94.08 mg/g at an initial concentration of 350 mg/L and adsorbent dosage of 0.05 g/25 mL. Freundlich and Langmuir's models fitted well with the results obtained from the experimental data. The pseudo-second-order model also suited the most for RhB adsorption with the most remarkable correlation coefficient ( R 2   =   0.934 ). The adsorption process was controlled by a chemisorption mechanism through electrostatic attraction, hydrogen bonding interactions, and π-π interactions.